Self-Effication in Relation to Personal Care and The Health-Related Quality of Life of Hemodialysis Patients - Diyah Candra Anita; Adelia Rizky Brilianti; Dwi Astuti; Sitti Fadhillah; Tuan Van Nguyen; Wantonoro Wantonoro (Faculty of Public Health, Hasanuddin University, Makassar, 2021)
Self-efficacy is important to ensure self-care to improve the health-related quality of life for hemodialysis patients. This study aimed to determine the relationship between self-efficacy and self-care and the health-related quality of life in hemodialysis patients. The research method was a quantitative correlation design with a cross-sectional approach. The instrument of the study was a questionnaire. A total sampling technique for 64 hemodialysis patients at RSUD (Regional Public Hospital) Wates Kulonprogo was used. Data analysis was conducted through the Kendall Tau test. It showed that 41 respondents (64.1%) were in the moderate category of self-efficacy, while 50 respondents (78.1%) were in the moderate category for the self-care aspect. The results of Kendall Tau analysis showed that self-efficacy was significantly associated with self-care (p= 0.004) and the health-related quality of life (p=0.041) for hemodialysis patients. It is expected that the nurse will periodically assess the biological and psychological aspects of hemodialysis patients.